IMPLEMENTASI MIKROKONTROLER ESP32 PADA ALAT PENYINARAN SCREEN SABLON PCB OTOMATIS BERBASIS IOT : IMPLEMENTASI MIKROKONTROLER ESP32 PADA ALAT PENYINARAN SCREEN SABLON PCB OTOMATIS BERBASIS IOT - Rafid Al Farisi; Paris Ali Topan; Titi Andriani; Muhammad Hidayatullah (Program Studi Teknik Elektro, 2023)
This study aims to find out how to manufacture and the effectiveness of using irradiation equipment screen IoT-based automatic screen printing using the ESP32 microcontroller. The first step in making a PCB is to iron the results of the circuit design on the PCB, which takes a long time. Therefore, a method for making PCBs with engineering is needed for screen printing to save time in the process of making paths on PCBs. In practice, technique screen This screen printing requires an irradiation process using light ultraviolet. Screen printing that has gone through the irradiation process will form a PCB path according to the desired pattern. Next, the pattern on screen printing can be directly used to form tracks on new PCBs by simply pouring ink on screen printing and rubbing over plain PCB. The PCB surface covered with screen printing ink will form a path on the PCB which is then ready for use. Based on the results of a comparison between making PCBs using the manual method with the method screen printing, the results obtained stated that the use of the method screen printing is very time and energy efficient in the process.